A Review on Big Data: Privacy and Security Challenges - Rohit Kumar (AG Volumes, 2022)
A significant rise in data is being generated due to factors such as the fast expansion and dissemination of the network services, the mobile devices, but also internet users. Almost every business is attempting to deal with the massive amounts of data that are being generated. The concept of big data has starting to gain traction. Traditional apps can’t handle huge data because it’s hard to store as well as analyse, so it poses serious privacy as well as security concerns. As a result, this article explores the scope of big data and reviews the most recent studies on security as well as privacy issues surrounding it. We’ll talk about the problems and the things that impact security. Privacy-preserving methods are also examined and expanded on in this paper.